2015
DOI: 10.1039/c5cp00800j
|View full text |Cite
|
Sign up to set email alerts
|

Controllable optical transitions of amorphous Mg and Mg–Ni films via electrochemical methods

Abstract: Amorphous Mg and MgNix (0.03 ≤ x ≤ 0.30) thin films capped with Pd were prepared by magnetron co-sputtering, and their hydrogen-induced optical transitions were investigated via electrochemical charging and discharging in KOH electrolyte solution. Repetitive transitions, up to dozens of times between the mirror state and transparent state, are achieved in these amorphous Mg and MgNix thin films even though some performance degeneration occurs during cycling. These deteriorations are mainly attributed to the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Theoretical calculations have indicated that MgH 2 thin layers with a thickness below 10 unit cells and MgH 2 particles with a grain size smaller than 1.3 nm would reduce the stability of MgH 2 . Alterations in hydrogen absorption/desorption properties were reported in Mg and its alloy thin films prepared by means of magnetron sputtering. It has been shown that in addition to nanosizing, the utilization of immiscible metals with Mg can modify the thermodynamics more effectively. A multilayer stack of Mg/Ti with a typical layer thickness below 10 nm revealed a large destabilization of MgH 2 due to the extra contribution of the interface energy difference Δγ between Mg/TiH 2 and MgH 2 /TiH 2 . For Ti-rich Mg–Ti alloy thin films and powders, nanometer-sized MgH 2 clusters coherently embedded in a TiH 2 matrix are formed upon hydrogenation, again resulting in enhanced destabilization of MgH 2 by the interface energy. , Recently, we succeeded in obtaining an even more destabilized MgH 2 by the addition of Cr to the Mg–Ti system: Cr is also immiscible with Mg and expected to increase the interface energy effect …”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations have indicated that MgH 2 thin layers with a thickness below 10 unit cells and MgH 2 particles with a grain size smaller than 1.3 nm would reduce the stability of MgH 2 . Alterations in hydrogen absorption/desorption properties were reported in Mg and its alloy thin films prepared by means of magnetron sputtering. It has been shown that in addition to nanosizing, the utilization of immiscible metals with Mg can modify the thermodynamics more effectively. A multilayer stack of Mg/Ti with a typical layer thickness below 10 nm revealed a large destabilization of MgH 2 due to the extra contribution of the interface energy difference Δγ between Mg/TiH 2 and MgH 2 /TiH 2 . For Ti-rich Mg–Ti alloy thin films and powders, nanometer-sized MgH 2 clusters coherently embedded in a TiH 2 matrix are formed upon hydrogenation, again resulting in enhanced destabilization of MgH 2 by the interface energy. , Recently, we succeeded in obtaining an even more destabilized MgH 2 by the addition of Cr to the Mg–Ti system: Cr is also immiscible with Mg and expected to increase the interface energy effect …”
Section: Introductionmentioning
confidence: 99%